Laparoscopic management of early stage primary fallopian tube carcinoma - Duraisamy, Kavitha Yogini; Balasubramaniam, Devi; Ravi, Karthikha; Balasubramanium, Aravinth (Indian Journal of Case Reports, 2019)
Primary fallopian tube cancer (PFTC) is a rare malignancy with an incidence of 0.14-1.8% of all genital malignancies. Presentationsof fallopian tube cancer are mostly nonspecific and include abdominal pain, profuse watery or serosanguinous discharge. Here, wepresent the case of a 51-year-old patient with FIGO stage 1A PFTC. It was diagnosed as hematosalpinx intraoperatively, during totallaparoscopic hysterectomy and diagnosed as PFTC on histopathology. Further management was by laparoscopic staging. A high indexof suspicion is needed in peri and postmenopausal women who present with unexplained uterine bleeding, profuse discharge, pelvicpain, adnexal mass or abnormal pap smear.